NH3-Plasma pre-treated carbon supported active iron–nitrogen catalyst for oxygen reduction in acid and alkaline electrolytes. Issue 6 (19th February 2020) - Mohan, Roopathy; Modak, Arindam; Schechter, Alex
Abstract : A new strategy in the synthesis of M–N–C type catalysts was introduced through the combination of plasma pre-treatment followed by conventional pyrolysis, which demonstrated higher ORR activity and stability than pristine M–N–C catalysts. Abstract : Metal–nitrogen–carbon (M–N–C) catalysts synthesized by a conventional high-temperature carbonization method are considered as promising electrocatalysts for the oxygen reduction reaction. Herein, we proposed a new approach for the preparation of M–N–C catalysts through NH3 -plasma pretreatment of high surface area black pearl carbon. In this study, a pre-treated carbon support facilitated the formation of an Fe–N–C (FeNC/NH3 –C) type model catalyst through pyrolysis, acid-treatment, and an additional pyrolysis step. In contrast to untreated FeNC/C, plasma pre-treated FeNC/NH3 –C contains Fe3 C and Fe–N x as active catalytic sites. XPS confirms the presence of a high surface concentration of FeN x (43.6%) on FeNC/NH3 –C that promotes low oxygen reduction overpotential (0.80 V vs. RHE in 0.5 M H2 SO4 and 1.0 V vs. RHE in 0.1 M KOH). Hence plasma activates the surface and incorporates nitrogen, which forms stable Fe–N coordination for accelerating oxygen reduction. Importantly, FeNC/NH3 –C shows a lower peroxide yield at 0.6 V vs. RHE (<1.0% in 0.5 M H2 SO4 and <2% in 0.1 M KOH) that can reduce the detrimental effect of H2 O2 on the catalyst support and exhibits high stability, as seen from thousands of potential cycling stability tests of FeNC/NH3 –C in acid solutions. Thereby this plasma-based new synthetic approach can promote more active and stable non-precious metal catalysts.